Mobile robotic platform IoT-based for LP gas detection (LACCEI, 2024)
The Internet of Things (IoT) is a revolutionary technological paradigm that has enabled communication with a large number of devices over the Internet. This article presents the design through the V-type methodology of a mobile robot that uses IoT platforms in order to navigate autonomously in indoor environments, with the possibility of detecting LP gas sources and sending the location of the leak through a GPS-sensor. The robot also includes a camera to obtain real-time video and monitor the inspection environment. The cloud platform allows the storage of data from the gas sensor and the location of the robot, as well as the transmission of commands between the server and the mobile robot through the use of a mobile application. The tests validate the functionality of the obtained mobile robotic platform.